2019
DOI: 10.2147/ijwr.s206401
|View full text |Cite
|
Sign up to set email alerts
|

<p>Chronic and acute effects of red wine versus red muscadine grape juice on body composition, blood lipids, vascular performance, inflammation, and antioxidant capacity in overweight adults</p>

Abstract: Purpose: Red wine may benefit health due to the presence of polyphenolic compounds. This research investigated effects of wine (W) versus grape juice (J) on body composition, blood lipids (cholesterol, HDL, LDL, and triglycerides [TG]), vascular responses (augmentation index [AIx] and central pulse wave velocity [cPWV]), inflammation (C-reactive protein [CRP]), and plasma antioxidant capacity (ferric-reducing ability of plasma [FRAP]) in sedentary individuals. Methods: In a randomized crossover design, 19 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…However, there was no significant difference between the red wine and de‐alcoholised red wine interventions, suggesting that the alcoholic matrix of wine did not affect the formation of phenolic metabolites by the gut microbiota ( P > 0.05) (Queipo‐Ortuno et al 2012). In contrast, other researchers have suggested that the presence of alcohol might be necessary to enhance the absorption of phenolic compounds present in wine (McAnulty et al 2019). The other six studies identified in the systematic review examined the effects of polyphenols from grape juice, wine or their extracts on the formation of polyphenolic metabolites.…”
Section: Potential Mechanisms Involved In Red Wine Gut Microbiota Anmentioning
confidence: 88%
“…However, there was no significant difference between the red wine and de‐alcoholised red wine interventions, suggesting that the alcoholic matrix of wine did not affect the formation of phenolic metabolites by the gut microbiota ( P > 0.05) (Queipo‐Ortuno et al 2012). In contrast, other researchers have suggested that the presence of alcohol might be necessary to enhance the absorption of phenolic compounds present in wine (McAnulty et al 2019). The other six studies identified in the systematic review examined the effects of polyphenols from grape juice, wine or their extracts on the formation of polyphenolic metabolites.…”
Section: Potential Mechanisms Involved In Red Wine Gut Microbiota Anmentioning
confidence: 88%